Economic feasibility of probiotic use in the diet of Nile tilapia, Oreochromis niloticus, during the reproductive period (Acta Scientiarum. Animal Sciences, 2020)
This work examines the economic advantages of probiotic use in the diet of Nile tilapia broodstock during the reproductive period. For this purpose, Bacillus subtilis was applied as a feed additive. The experimental design was completely randomized with three treatment groups: the T0 control (without probiotic), the T1 continuous probiotic intake, and the T2 alternate probiotic intake at a dose of 0.50 g kg-1 of feed (1010 CFU g-1) with four replicates. For the reproduction assay, 118 females and 48 males of Nile tilapia (proportion 4 males:9 females. hapa-1) (weight 527.65 g ± 185.98 g and length 30.16 cm ± 3.57 cm) were distributed into 12 hapas (3.5 Ã— 2.0 Ã— 1.5 m). Reproductive variables (spawning female percentage, egg production, and fry production) were used to calculate the economic feasibility indexes (total cost of nutrition [TcN], gross revenue [GR], and total operational profit [ToP]). The results show increasing values for spawning female number, collected eggs, and surviving fry in the probiotic groups. We recommend continuous intake of probiotic (feed with addition of probiotic) at a dose of 0.5 g kg-1 of feed (1010 CFU g-1) during the breeding season of Nile tilapia, due to the suitable reproductive indexes and profitability.